Pengaruh Penyuluhan Tentang Keputihan Menggunakan Media Leaflet Terhadap Pengetahuan dan Sikap Remaja Putri di SMAS Sinar Kasih Sintang Tahun 2023 - Fetty Aprianti; Ria Damayanti; Rika Yuanita Pratama; Nurul Khoirun Nisa (Jurnal Medika Nusantara, 2025)
Leucorrhoea is all the genital discharge that is not blood. Leucorrhoea cases, based on data from the Tanjung Puri Health Center, are 20 cases in 2020, 22 cases in 2021 and 32 cases in 2022, vaginal discharge in adolescents can cause the reproductive organs to be susceptible to infection and can even cause cancer and infertility if not handled properly. This study aims to determine the effect of counseling about vaginal discharge on the knowledge and attitudes of young women at SMAS Sinar Kasih Sintang. Research This research is a quantitative experimental research with pre-experimental research using a one group pretest-posttest design approach. The results of the study were analyzed using a non-parametric statistical test, namely the Wilcoxon signed rank test to see the effect of counseling on knowledge and attitudes of young women. The results showed that there was an effect of counseling with an increase in knowledge of 2.6 (p-value=0.000) and an increase in attitude of 8.06 (p-value=0.000). That is, there are differences in knowledge and attitudes of young women before and after counseling about vaginal discharge. There is an effect of counseling on vaginal discharge on the knowledge and attitudes of young women at Senior Hight School Sinar Kasih Sintang Regency 2023